Genotoxic and mutagenic effects of triterpenes: A mini-review - Islam, Muhammad (International Journal of Medicine, 2017)
This review sketches genotoxic and mutagenic potentials of triterpenes, which find outs some important genotoxic, mutagenic as well as non-genotoxic and non-mutagenic triterpenes. Triterpeners are the important natural products.